H i intensity mapping with MeerKAT: power spectrum detection in cross-correlation with WiggleZ galaxies. Issue 4 (31st October 2022) - Cunnington, Steven; Li, Yichao; Santos, Mario G; Wang, Jingying; Carucci, Isabella P; Irfan, Melis O; Pourtsidou, Alkistis; Spinelli, Marta; Wolz, Laura; Soares, Paula S; Blake, Chris; Bull, Philip; et al.
ABSTRACT: We present a detection of correlated clustering between MeerKAT radio intensity maps and galaxies from the WiggleZ Dark Energy Survey. We find a 7.7σ detection of the cross-correlation power spectrum, the amplitude of which is proportional to the product of the ${\rm H}\, {\small I}$ density fraction ($\Omega _{{\rm H}\, {\small I}}$ ), ${\rm H}\, {\small I}$ bias ($b_{{\rm H}\, {\small I}}$ ), and the cross-correlation coefficient ( r ). We therefore obtain the constraint $\Omega _{{\rm H}\, {\small I}}b_{{\rm H}\, {\small I}}r\, {=}\, [0.86\, {\pm }\, 0.10\, ({\rm stat})\, {\pm }\, 0.12\, ({\rm sys})]\, {\times }\, 10^{-3}$, at an effective scale of $k_{\rm eff}\ {\sim }\ 0.13\, h\, \text{Mpc}^{-1}$ . The intensity maps were obtained from a pilot survey with the MeerKAT telescope, a 64-dish pathfinder array to the SKA Observatory (SKAO). The data were collected from 10.5 h of observations using MeerKAT 's L -band receivers over six nights covering the 11 h field of WiggleZ, in the frequency range 1015–973 MHz (0.400 $\, {\lt }\, z\, {\lt }\, $ 0.459 in redshift). This detection is the first practical demonstration of the multidish autocorrelation intensity mapping technique for cosmology. This marks an important milestone in the roadmap for the cosmology science case with the full SKAO.